2015
DOI: 10.1007/s10853-015-9035-8
|View full text |Cite
|
Sign up to set email alerts
|

Stable antifouling coatings by hydrogen-bonding interaction between poly(2-methyl-2-oxazoline)-block-poly(4-vinyl pyridine) and poly(acrylic acid)

Abstract: Surface modified with so-called protein-repellent or antifouling polymers has become indispensable for the development of modern therapeutic and diagnostic medical devices. In this work, a series of novel well-defined poly(2-methyl-2-oxazoline)-block-poly(4-vinyl pyridine) (PMOXA-b-P4VP) diblock copolymers were synthesized by using copper-catalyzed azide-alkyne cycloaddition reaction of a-alkynyl-PMOXA and x-N 3 -P4VP, in which a-alkynyl-PMOXA and x-N 3 -P4VP were prepared by cationic ring opening polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 43 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Antifouling properties of the obtained brushes with three different molecular weights were assessed following a previously reported protocol. 29 Initially, the PEG brush modified substrates were equilibrated in PBS buffer (pH 7.4) for 2 h and then immersed in a solution of BSA-FITC (0.25 mg/mL in PBS) at room temperature. Two hours later, the substrates were rinsed with PBS buffer and then DI water before being dried with argon.…”
Section: Synthesis Of Peg Brushes On the Dibo-modified Siliconmentioning
confidence: 99%
“…Antifouling properties of the obtained brushes with three different molecular weights were assessed following a previously reported protocol. 29 Initially, the PEG brush modified substrates were equilibrated in PBS buffer (pH 7.4) for 2 h and then immersed in a solution of BSA-FITC (0.25 mg/mL in PBS) at room temperature. Two hours later, the substrates were rinsed with PBS buffer and then DI water before being dried with argon.…”
Section: Synthesis Of Peg Brushes On the Dibo-modified Siliconmentioning
confidence: 99%
“…3 For instance, initiating the chain with propargyl tosylate introduces an alkynyl functionality at the α-end that can be used for CuAAC post-polymerization functionalization or thiol−yne reactions. 4 Alternatively, the growing chain end can be terminated with acrylic acid, installing an alkenyl functionality on the chain end, which can subsequently be reacted in a thiol−ene reaction for polymer−polymer coupling. 5 Additionally, the side group of 2-oxazoline can be utilized to introduce functional groups, which allow for tuning the physical properties of the polymer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of functional initiators and a broad range of terminating agents allow for a variety of functionalities to be introduced at the poly­(2-oxazoline) chain ends, which can further undergo postpolymerization reactions . For instance, initiating the chain with propargyl tosylate introduces an alkynyl functionality at the α-end that can be used for CuAAC post-polymerization functionalization or thiol–yne reactions . Alternatively, the growing chain end can be terminated with acrylic acid, installing an alkenyl functionality on the chain end, which can subsequently be reacted in a thiol–ene reaction for polymer–polymer coupling .…”
Section: Introductionmentioning
confidence: 99%
“…hydrophilicity and biocompatibility) to PEG and less degradation than PEG. [25][26][27][28][29] Cavallaro and coworkers reported that the films developed via plasma deposition of 2-methyl-2-oxazoline (MOXA) could resist the adsorption of Staphylococcus epidermidis and cells by more than 90% regardless of the type of substrate used. 30 Bai and coworkers developed poly(2-methyl-2-oxazoline-random-glycidyl methacrylate) (PMOXA-r-GMA) comb copolymers.…”
Section: Introductionmentioning
confidence: 99%